(untitled) (International Journal of Food and Nutritional Sciences, 2022)
BACKGROUND AND PURPOSE: Thisresearch has beenconducted for comparing the difference between the impacts ofactive chin tuck exercises versus versatile muscle therapy with ultrasound therapy insubjects with neck pain. DESIGN:Quasi-experimentalstudydesign METHODS: 30 computer experts between the ages of 20 and 40 who met the requirements were chosen at random and divided into two groups, each with 15 subjects. Group A was assigned to Active chin tuckexercise with Ultrasound therapy and Group B to Versatile muscle therapy (using a sub-occipital release tool)with Ultrasoundtherapy. The research has been completed in a period of 3 weeks. Before and after the intervention, neck functionality and range of motion were assessed using the Copenhagen Neck Functional Disability Scale and the Goniometer, respectively, and the results were evaluated. Result: The study showed an improvementinNeck function andan increase in ROM among desktop professionals treatedwithActivechin tuck exercises with Ultrasound therapy & also in groups treated with Versatilemuscletherapywith Ultrasound therapyfor patients with cervical pain.It is concluded thatActive chin tuck exercise withUltrasound therapyrevealed an improvementinneckfunction and Range of Motion.